2015
DOI: 10.1371/journal.pone.0133048
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Selected Methanogens, Fibrolytic Bacteria, and Proteobacteria in the Gastrointestinal Tract of Neonatal Dairy Calves from Birth to 72 Hours

Abstract: The microbial communities in the gastrointestinal tract of a young calf are essential for the anatomical and physiological development that permits a transition from milk to solid feed. Selected methanogens, fibrolytic bacteria, and proteobacteria were quantified in the rumen fluid and tissue, abomasum fluid, cecum fluid and tissue, and feces of Holstein bull calves on day 0 (0–20 mins after birth), day 1 (24 ± 1 h after birth), day 2 (48 ± 1 h after birth), and day 3 (72 ± 1 h after birth). Methanogens, fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 43 publications
6
109
0
1
Order By: Relevance
“…2e). In agreement with previous studies 5,18,45,46 , members of these fiberdegrading families appear on the first day of life and increase in relative abundance before the consumption of plant fiber diet. This could suggest a potential inoculation and maintenance mechanism of the rumen ecosystem with these seminal microbial families.…”
Section: Resultssupporting
confidence: 92%
“…2e). In agreement with previous studies 5,18,45,46 , members of these fiberdegrading families appear on the first day of life and increase in relative abundance before the consumption of plant fiber diet. This could suggest a potential inoculation and maintenance mechanism of the rumen ecosystem with these seminal microbial families.…”
Section: Resultssupporting
confidence: 92%
“…These taxa were present as early as 1 week of age, when calves had been exposed only to liquid feeds, including colostrum and milk. This supports a model of colonization by potentially beneficial digestive bacteria across the calf GIT very early in life, even in the absence of solid dietary substrates (2,3).…”
Section: Discussionsupporting
confidence: 80%
“…The rumen methanogenic communities of newborn calves carry a metabolic potential facilitated by environmental factors A methanogenic community in the rumen at early stages of bovine development has been reported to appear as early as 20 min after birth (Guzman et al, 2015). Nevertheless, questions remain as to whether during the early developmental stages the population is alive and has the potential for methanogenic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Early acquisition and establishment of methanogenic communities in ruminants has been reported to occur a few days after birth (Fonty et al, 1987;Minato et al, 1992;Morvan et al, 1994;Skillman et al, 2004). More recent studies have revealed that methanogenic cells can be found in the calf rumen as early as 20 min after birth (Guzman et al, 2015). However, questions remain as to their actual functionality in the first days of life, their viability and substrate requirements for methanogenesis during the initial stages of rumen colonization, when environmental conditions are vastly different from those of the mature rumen ecosystem.…”
Section: Introductionmentioning
confidence: 99%